2006
DOI: 10.1159/000095759
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Cerebral Embolic Load and Postoperative Cognitive Dysfunction in Cardiac Surgery

Abstract: Background: The aim of the study was to determine the effects of asymmetric cerebral embolic load on cognitive functions. Methods: Thirty-six open heart surgery (OH) and 26 coronary artery bypass grafting (CABG) patients were evaluated by neuropsychological and transcranial Doppler tests. Results: OH was associated with a significantly larger microembolic load in comparison to CABG. In OH patients, the microembolic load at the left middle cerebral artery correlated with a verbal memory decline, whereas the mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
1
5

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 36 publications
4
27
1
5
Order By: Relevance
“…[5][6][7][8] Considering any thrombus inside the LVAD pump as a part of cardiac embolic material in addition to actual intracardiac thrombi, right-to-left propensity of stroke after LVAD can be easily explained by anatomic alignment of the arteries arising from aortic arch. Moreover, surgical manipulation of LVAD outflow cannula-to-ascending aorta anastomosis may also direct embolic material toward the brachiocephalic trunk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8] Considering any thrombus inside the LVAD pump as a part of cardiac embolic material in addition to actual intracardiac thrombi, right-to-left propensity of stroke after LVAD can be easily explained by anatomic alignment of the arteries arising from aortic arch. Moreover, surgical manipulation of LVAD outflow cannula-to-ascending aorta anastomosis may also direct embolic material toward the brachiocephalic trunk.…”
Section: Discussionmentioning
confidence: 99%
“…2,4 Cerebral embolic events after cardiac surgery are frequently distributed more often in the right cerebral hemisphere. [5][6][7] Kim et al 8 reported recently that right hemispheric infarcts are associated with cardiogenic embolism, whereas left hemispheric infracts are more associated with aortogenic embolism. In the present study, we investigated the distribution of stroke in patients undergoing LVAD implantation and whether clinical characteristics differed in LVAD patients experiencing right versus left hemispheric stroke.…”
mentioning
confidence: 99%
“…In our original study which using intraoperative transcranial doppler monitoring [56], we registered significant linear correlations between the intraoperative microembolic load on the left hemisphere and postoperative decline of performance on digit span forward, but we did not observe this on the “word-list learning” or “story learning” tests. In addition, we observed significant correlations between intraoperative microembolic loads on the right hemisphere and a decline on “nonverbal memory” tests.…”
Section: Introductionmentioning
confidence: 70%
“…Whereas some study groups described a preponderance of left-sided MESs, 50,90 others either reported an equal distribution of MESs 91 or found a preference for the right hemisphere. 49,51 In conclusion, MESs are a common phenomenon during cardiac surgery. The composition of the microemboli is heterogeneous and reflects solid and gaseous particles.…”
Section: Monitoring Of Mess During Cardiac Surgerymentioning
confidence: 91%
“…Interestingly, a specific verbal memory decline in patients with predominantly left-sided MESs was observed, whereas a higher number of right-sided MESs was associated with a nonverbal memory deficit after open-heart surgery. 51 The correlation of a high number of MESs, particularly during on-pump cardiac surgery, with a relative reduction of prefrontal activation during functional magnetic resonance imaging while performing verbal memory tasks 4 weeks postoperatively could also be demonstrated. 52 There are additional reports on cognitive impairment and delayed recovery after CABG due to intraoperative MESs.…”
Section: Monitoring Of Mess During Cardiac Surgerymentioning
confidence: 93%